1999
DOI: 10.1007/bf03343579
|View full text |Cite
|
Sign up to set email alerts
|

White Addison’s disease: What is the possible cause?

Abstract: A case of chronic primary adrenal insufficiency without hyperpigmentation in a 64-year-old woman is reported. Due to the absence of hyperpigmentation the diagnosis was delayed and she became critically ill. During endocrine evaluation, in order to investigate the mechanism responsible for the absence of hyperpigmentation, skin biopsy was done and hormones responsible for the skin pigmentation were measured. Absence of hyperpigmentation is explained by high degree of melanosome degradation in secondary lysosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 5 publications
0
8
0
1
Order By: Relevance
“…APS 2 is a polygenic disorder that produces polymorphisms that may increase the risk or protect against autoimmune diseases. For example, molecules of the major histocompatibility complex, such as DR and DQ, are associated with the development of the autoantibodies against hydroxylase that are associated with the clinical progression of adrenal failure, and HLA‐B15 is associated with the protection of the progression of adrenal insufficiency in individuals with positive 21‐hydroxylase autoantibodies …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…APS 2 is a polygenic disorder that produces polymorphisms that may increase the risk or protect against autoimmune diseases. For example, molecules of the major histocompatibility complex, such as DR and DQ, are associated with the development of the autoantibodies against hydroxylase that are associated with the clinical progression of adrenal failure, and HLA‐B15 is associated with the protection of the progression of adrenal insufficiency in individuals with positive 21‐hydroxylase autoantibodies …”
Section: Discussionmentioning
confidence: 99%
“…For example, molecules of the major histocompatibility complex, such as DR and DQ, are associated with the development of the autoantibodies against hydroxylase that are associated with the clinical progression of adrenal failure, and HLA-B15 is associated with the protection of the progression of adrenal insufficiency in individuals with positive 21-hydroxylase autoantibodies. 9 Salinas-Santander et al 10 evaluated 198 Mexican patients with vitiligo and found an association of it with the presence of autoimmune thyroid disease in 23% of these patients. To our knowledge, there is no report of an HLA association in a Mexican family with APS 2 in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…All such cases have been recorded in Europeans with fair skin, which suggests that MC1R variants could be implicated; in many instances, diagnosis was unexpected or delayed because of the absence of pigmentation. In only one patient was a mechanism for the absence of hyperpigmentation proposed; it was attributed to generalized vitiligo, with a high degree of melanosome degradation in secondary lysosomes being reported in a skin biopsy (15). …”
Section: Discussionmentioning
confidence: 99%
“…14 Tiryaki ve Özkorumak, bildirdikleri olguda hiperpigmentasyon tespit ettiklerine dikkat çekmişlerdir. 13 Bu nedenle depresyonun bedensel ve fiziksel belirtilerinin ön planda olduğu hastalarda ayrıntılı bir fizik muayene ile saptanacak hiperpigmentasyon, tanının atlanmamasını sağlayabilir.…”
unclassified